PERAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MI MATHLA’UL ANWAR MADA JAYA KABUPATEN PESAWARAN: Indonesia - Mohammad Masrur; Nur Kholis; Nurhadi Kusuma (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2023)
Abstract Headmaster have an important role in improving the quality of education. This study aims to determine the extent of the role of the head of MI Mathla'ul anwar Mada Jaya Pesawaran Regency in improving the quality of education. This type of research is included in qualitative descriptive research. Methods of data collection using interviews and observation. The data analysis technique uses three steps, namely data reduction, data presentation, and conclusions. The results of the study stated that the head of MI Mathla'ul Anwar Mada Jaya had worked hard to improve the quality of education by taking on the role of educator, administrator, manager, supervisor, and motivator although there were several roles that had not emerged, namely innovator. The role as a leader is reduced in his role as a manager, supervisor, and motivator. Key words: Role, Headmaster